The efficacy and safety of estriol to treat vulvovaginal atrophy in postmenopausal women: a systematic literature review. (4th July 2017) - Rueda, C.; Osorio, A. M.; Avellaneda, A. C.; Pinzón, C. E.; Restrepo, O. I.
Abstract: Objectives: To evaluate the efficacy and safety of estriol for the treatment of vulvovaginal atrophy in postmenopausal women. Methods: A systematic literature review was performed. We searched the following electronic databases: Medline, Cochrane, Embase, Lilacs, CINHAL and Google Scholar. The studies selected included controlled clinical trials and quasi-experimental studies. Selections were made in pairs and independently, first by title and abstract and then complete texts. Results: We identified 188 studies, 22 of which met the inclusion criteria; 13 were controlled clinical trials and nine were quasi-experimental, and 1217 women were included. These studies confirmed the efficacy of local estrogens to treat symptoms of vulvovaginal atrophy with few adverse effects reported. Following treatment, serum estriol levels rose, peaking at 1 h. At the 6-month follow-up, there was no increase in serum estriol in treated women. Conclusions: The available evidence (of low and moderate quality) shows that, when administered vaginally, estriol preparations appear to be safe for women who have risk factors related to systemic estrogen therapy.